ANALISIS EKSISTING JALAN KESATRIAN AKADEMI MILITER GUNA KELANCARAN MOBILISASI TARUNA - Satrio Raihan HS; Agung Prapsetyo; M. Zain Triputra; Budi Mawardi Syam (PPM Sdirjianbang Akademi Militer, 2023)
The Military Academy is an educational institution for the Army to educate prospective Army officers. The places in the Military Academy are connected by existing roads. As a result of the large number of road uses for these vehicles, it causes frequent congestion on certain roads in the Military Academy. Crowded roads are not only caused by the large number of vehicle users, but can be caused by cadets who are moving places using these roads which are often disrupted due to the roads in the Military Academy not being standard. The purpose of this study is to determine the existing condition of the road at the Military Academy and to analyze the approach to find the ideal road and to analyze the efforts that can be made to overcome road problems at the Military Academy. This study uses qualitative research methods with a literacy approach and field observations. The source of data in this study is primary data obtained through direct observation and measurement on roads at the Military Academy. While secondary data comes from literature and journals that support the completion of this Final Project. The results of the research are that the condition of the roads in the Military Academy are still many that do not meet the standards for the needs of road users, so it is necessary to regulate road functions and repair roads to overcome road problems in the Military Academy.